Validity of Rubiaceae ethnobotany popular science book for developing students' critical thinking skills - Nurul Fajriyah; Muhammad Zaini; Badruzsaufari Badruzsaufari (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2026)
The use of teaching materials based on local potential among university students remains limited; therefore, a popular science book has been developed to enhance students’ critical thinking skills, thereby assisting them in higher education or the workforce. This study aims to describe the validity and practicality of the content of the Popular Science Book (PSB) on the ethnobotany of the Rubiaceae family among the Dayak Bakumpai community for training students’ critical thinking skills. This study employed Education Design Research (EDR) using Tessmer’s formative evaluation, limited to expert validation and one-to-one testing. The research data consisted of validator questionnaire forms and content appeal (practicality) questionnaire forms. The results of this study yielded a validity score of 91.03 (highly valid) and a content practicality score of 92.95 (very good). Based on these results, it is concluded that the BIP is suitable and practical for use as teaching material based on local potential that is relevant to students’ needs in developing critical thinking skills. Abstrak. Penggunaan bahan ajar pada mahasiswa berbasis potensi lokal masih belum banyak sehingga dikembangkan buku illmiah popular yang dapat meningkatkan keterampilan berpikir kritis mahasiswa untuk membantu mahasiswa dalam Tingkat Pendidikan lanjutan ataupun dunia kerja. Penelitian ini bertujuan mendeskripsikan validitas dan kepraktisan isi Buku Ilmiah Populer (BIP) etnobotani famili Rubiaceae masyarakat Dayak Bakumpai untuk melatih keterampilan berpikir kritis mahasiswa. Jenis penelitian ini menggunakan Education Design Research (EDR) dengan evaluasi formatif Tessmer yang dibatasi hingga uji validasi ahli dan uji perorangan (one-to-one). Data penelitian ini berupa lembar angket validator dan lembar angket daya Tarik (kepraktisan isi). Hasil penelitian ini memperoleh hasil validitas sebesar 91,03 (sangat valid) dan hasil kepraktisan isi sebesar 92,95 (sangat baik). Berdasarkan hasil penelitian ini disimpulkan bahwa BIP layak dan praktis untuk digunakan sebagai bahan ajar berbasis potensi lokal yang relevan dengan kebutuhan mahasiswa dalam melatih keterampilan berpikir kritis.